Primary thyroid squamous cell carcinoma: a challenging management problem - Agilinko, Joshua (BMJ Case Rep, 2021)
Primary thyroid squamous cell carcinoma (SCC) is a rare and highly aggressive cancer. Diagnostic work-up encompasses cervical ultrasonography, tissue biopsy and CT scan. Surgery, radiotherapy and chemotherapy are the available treatment modalities. With a mean survival rate of 7 months reported in the literature, our patient is alive 2 years after successful treatment of her advanced primary thyroid SCC with surgery and radiotherapy.